Hyperprogression on anti-PD-1 treatment. Is subsequent therapy feasible? A case report and review of the literature - Jan Skacel; Bohuslav Melichar; Beatrice Mohelnikova-Duchonova; Radmila Lemstrova (Biomedical Papers, 2023)
Background. Hyperprogressive disease (HPD) is a new phenomenon that has emerged in the immunotherapy era. HPD is defined as a rapid tumour growth with detrimental effect on the patient condition and disease course. The management and treatment following HPD is not defined. We present here the case report of patient with HPD and review of the literature on putative mechanisms of HPD and following disease management. Methods and Results. A 60-year old male patient with metastatic melanoma was indicated for systemic treatment with anti-programmed cell death (PD)-1 antibody. Rapid tumour growth and detrimental effect on the patient general condition after administration of a single dose of anti-PD-1 antibody met the criteria of HPD. The patient underwent the second line taxane-based chemotherapy with good tolerance and disease stabilization. The third line treatment with anti- cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4) antibody ipilimumab was well tolerated and resulted in partial response. Re-challenge with anti-CTLA-4 antibody was feasible, but only with a modest clinical effect. Conclusion. Prompt recognition of HPD and administration of salvage chemotherapy with taxane-based regimens may be crucial. HPD is rarely observed with ipilimumab treatment. Administration of ipilimumab as well as an ipilimumab re-challenge are feasible after HPD on anti-PD-1 antibodies. Investigation of new predictive biomarkers of HPD is warranted as well as new agents that potentiate the immune response in patients affected with this insidious complication.